Innovative teaching strategies, school quality as predictors of students’ achievement in junior secondary school civic education in Abeokuta metropolis (2017)
The research investigated innovative teaching strategies, school quality as predictors of students' achievement in junior secondary school civic education in Abeokuta metropolis. Multistage sampling techniques were adopted in selecting two Local government Areas in Abeokuta, five hundred (500) students offering Civic Education and thirty (30) teachers. Four research questions were raised and answered with three validated instruments; Innovative Teaching Method Questionnaire (r =.69); School Quality Questionnaire (r =. 75); Civic Education Achievement Test (CEAT), guided the study. Data obtained were analysed using Pearson Product Moment Correlation and multiple regressions at 0.05 level of significance. Results indicated that relationship exists between innovative teaching strategies and students' achievement in civic education (r = .169, p < 0.05(.017)). Also, the finding revealed that school quality was significant on students' achievement in civic education (r = .312, p < 0.05(.000)). Apart from, the earlier mentioned findings all the variables jointly explained 10% of the variance observed in students' achievement in civic education. Further, results showed, that school quality (6 - .288, t 4.156, p < 0.05(.000) contribute positively significant in the prediction of students' achievement in civic education. However, innovative teaching strategies (6 = 0.100, t 1.435, p > 0.05(.153)) contributed positively but insignificantly in the prediction of students' achievement in civic education. This is an indication that school quality actually predicted students' achievement in civic education. The paper therefore recommended that: teachers should be exposed to available innovative teaching strategies through workshop and seminars to ensure desirable students' achievement in civic education.